Synthesis and biological activity of ampicillin derivatives - Liak, Amanda Man Dee (Universiti Malaysia Sarawak, UNIMAS, 2012)
Ampicillin is a beta-lactam antibiotic that has been widely used clinically to treat bacterial infections particularly pathogens such as Escherichia coli. This research focused on the synthesis of ampicillin derivatives by covalently linking its amine bond through condensation reaction to isomers of hydroxybenzlaldehyde (2-hydroxybenzaldehyde, 3-hydroxybenzaldehyde, and 4-hydroxybenzaldehyde) as well as 2,4-dimethoxybenzaldehyde. Five ampicillin derivatives compound have been synthesized. The synthesized compounds were characterized using FTIR, 1HNMR and 13CNMR. The antibacterial activity was evaluated according to its zone of inhibition and minimum concentration value using turbidimetric method against the growth of Escherichia coli. However, the results indicated that the synthesized compound did not exhibit any significant antibacterial activity against Escherichia coli. The effects of the structure of the investigated compounds on the antibacterial activity were discussed.